The effectiveness of Canva-based learning media in the subject of vocational basics for grade X agribusiness crops at SMKN 3 Sidenreng Rappang - Ramlan Ramlan; Firman Firman; Suardi Zain; Jusman Tang (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effectiveness of Canva-based learning media in improving the learning outcomes of Grade X Agribusiness Crops students at SMKN 3 Sidenreng Rappang in the subject of Vocational Basics. The research method used is an experimental method with a one-group pretest-posttest design. The instruments used have passed both validity and reliability tests. The results of the study show a significant improvement in students’ learning outcomes after using Canva media in the learning process, with an average pretest score of 50.36 and a posttest score of 93.73. The T-test results show a sig. (2-tailed) value of 0.000 < 0.05. Thus, the use of the Canva application is effective in improving students' learning outcomes in vocational basic material. Canva has also been proven to qualitatively increase students' motivation and engagement during the learning process.